Weather Changes and Impacts on Agriculture in Rural Areas: Mitigation and Adaptation Efforts - Rachma Putri Dwi Amalia; Nur Suci Putri Solikati; Tegar Prasetyo Utomo; Rizqi Rakhmadhani Zahya; Istifarin Herdiana Fitrah (Proceeding International Conference Restructuring and Transforming Law, 2024)
One of the biggest obstacles in rural farming is changes in weather. The impact of severe weather changes can include increasing temperatures, unpredictable rainfall, long dry seasons, and natural disasters that occur more frequently. This impact can be significant on agricultural productivity and prosperous farmers in rural areas. Therefore, there is a need for adaptation and mitigation efforts to overcome the impacts of weather changes. Adaptation can be achieved by improving farmers' skills in managing natural resources, using technology that is more environmentally friendly, and improving agricultural practices that are more sustainable for the future. Apart from that, mitigation can be done by implementing effective processing practices for agricultural waste.